The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2325967120909385
|View full text |Cite
|
Sign up to set email alerts
|

Injury-Related Fears During the Return-to-Sport Phase of ACL Reconstruction Rehabilitation

Abstract: Background: Fear of reinjury is common after anterior cruciate ligament reconstruction (ACLR) and often deters a return to preinjury sport participation. A better understanding of injury-related fear is needed to inform rehabilitation strategies. Purpose/Hypothesis: The purpose of this study was to (1) identify individual fear-evoking tasks or situations, (2) compare the intensity and amount of change relative to other injury-related fears (reinjury, knee giving way, and knee pain) after completion of a return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…The more active the patients are to participate, the better the training effect will be. Rehabilitation training should maximize the number of repetitions of training and maximize the active efforts of patients, which is one of the most widely accepted principles in the field of rehabilitation clinical and rehabilitation engineering [ 8 ]. However, in the robot-assisted rehabilitation training, the robot mainly adopts an adaptive control algorithm to assist the patient, which allows the patient to reduce their active efforts, which leads to the patient slackening, inertia, and reduced rehabilitation effect.…”
Section: Introductionmentioning
confidence: 99%
“…The more active the patients are to participate, the better the training effect will be. Rehabilitation training should maximize the number of repetitions of training and maximize the active efforts of patients, which is one of the most widely accepted principles in the field of rehabilitation clinical and rehabilitation engineering [ 8 ]. However, in the robot-assisted rehabilitation training, the robot mainly adopts an adaptive control algorithm to assist the patient, which allows the patient to reduce their active efforts, which leads to the patient slackening, inertia, and reduced rehabilitation effect.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with findings of no change in TSK-11 scores after plyometric training administered at an earlier timeframe post ACLR, 24 and persistent injury-related fears after advanced training. 26 Further research is needed to determine alternative ACLR rehabilitation approaches to address injury-related fear. It is possible that graded exposure treatment approach, which identifies and hierarchically exposes patients to their specific fear, might be needed to address injury-related fear as it has shown benefit for other fears and phobias.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] These programs usually target the 6-12 months postoperative time period and generally include lower extremity strengthening and neuromuscular training (agility, perturbations and/or plyometrics) at an increased intensity level compared to standard rehabilitation. 16,23 Research has shown that potential benefits of advanced training include improved function, [22][23][24] improved passing rate on return to sport criteria consisting of physical impairment and psychological measures, 16 and possibly prevention of secondary (re)-injury 22,25 Even without an explicit psychological intervention, previous studies have shown that patients who complete advanced training have improved overall psychological readiness for sport participation 26 and improved selfefficacy for knee-related activities. 24 To our knowledge, no study has directly compared physical and psychological outcomes in patients that did or did not participate in advanced training during the return to sport phase following ACLR.…”
Section: Introductionmentioning
confidence: 99%
“…36 From a psychological perspective, the return-to-sport phase after ACL reconstruction surgery has been shown to be particularly challenging for some athletes, as negative emotions can be heightened at this time and can even lead to an avoidance of return to play. 3,24 It has been estimated that up to half of athletes do not return to competitive sport after ACL reconstruction surgery. 2 Published in 2008, the Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI) scale was developed as a tool to evaluate psychological readiness to return to sport after ACL injury, and it is currently the only scale specific to ACL injury.…”
mentioning
confidence: 99%